A relação entre o idoso e o seu cuidador em situações de violência - Barreto, Danyella da Silva (Universidade do Vale do Rio dos Sinos, 2011)
Violence against the elderly is a topic of relevance to public health, largely due to the 60 years and older population growth. This study aimed to make a bibliographic review on the subject of elder abuse in the period 2005 to 2010. The databases consulted were: LILACS, SciELO, MEDLINE, ISI Web of Knowledge and Academic Search Premier. A total of 1098 articles were found. After excluding documents that were not articles, were not available in full text, repeated material and material that did not addressed directly the issue, remaining 211 articles were analyzed according to the type of study, country of origin and the most studied sub themes within the major topic of violence against the elderly. There was a predominance of quantitative studies and, between countries, the United States was the country that most published. The most studied sub themes were grouped into the following categories: 1) prevalence studies; 2) risk and protection factors for abuse; 3) instruments’ diagnosis and validation; 4) perceptions about elder abuse; 5) consequences of abuse; and 6) prevention and Intervention in situations of abuse.
Keywords: Abuso; Idoso; Maus-tratos ao idoso; Violência contra o idoso; Elder; Abuse; Elderly abuse; Elder mistreatment; ACCNPQ::Ciências Humanas::Psicologia